A complete absence of indirect genetic effects on brain gene expression in a highly social context. Issue 21 (18th September 2022) - Kay, Tomas; Alciatore, Giacamo; La Mendola, Christine; Reuter, Max; Ulrich, Yuko; Keller, Laurent
Abstract: Genes not only control traits of their carrier organism (known as direct genetic effects or DGEs) but also shape their carrier's physical environment and the phenotypes of their carrier's social partners (known as indirect genetic effects or IGEs). Theoretical research has shown that the effects that genes exert on social partners can have profound consequences, potentially altering heritability and the direction of trait evolution. Complementary empirical research has shown that in various contexts (particularly in animal agriculture) IGEs can explain a large proportion of variation in specific traits. However, little is known about the general prevalence of IGEs. We conducted a reciprocal cross‐fostering experiment with two genetic lineages of the clonal raider ant Ooceraea biroi to quantify the relative contribution of DGEs and IGEs to variation in brain gene expression (which underlies behavioural variation). We found that thousands of genes are differentially expressed by DGEs but not a single gene is differentially expressed by IGEs. This is surprising given the highly social context of ant colonies and given that individual behaviour varies according to the genotypic composition of the social environment in O. biroi . Overall, these findings indicate that we have a lot to learn about how the magnitude of IGEs varies across species and contexts.